(untitled) (Islas, 2022)
ABSTRACT Introduction: The article presents an assessment of the figure of Ramiro Guerra y Sánchez given not only by its author but also by valuable intellectuals contemporary with Guerra such as Carlos Rafael Rodríguez, Raúl Roa, Medardo Vitier, Fernando Ortiz, Emilio Roig de Leuchsenring. Methods: In this study about Ramiro Guerra, a distinction of his intellectual productionis made along two main lines: the texts with pedagogical content and critical analysis to Cuban education and the historiographic essay. Results: Specifically, the author pauses in the analysis of two works considered «minor» within his historiographical task: Mudos Testigos (1948) and Por las veredas del Pasado (1957), which demonstrate the valuable contribution of Ramiro Guerra to the social, regional and rural family history in Cuba between the end of the 19.th century and the beginning of the 20.th century. Conclusions: The conclusions are aimed at placing Ramiro Guerra in a very important position within the Cuban intelligentsia of the 20.th century and to understand his validity in Cuban historical studies.